Attractiveness of Forest Research Institute Malaysia (FRIM) Canopy Walkway as a nature-based tourism product - Ramlan, Mohd Aswad; Aziz, Azlizam; Mariapan, Manohar; Bidin, Sheena; Yacob, Mohd Rusli (Forestry Department Peninsular Malaysia, 2013)
FRIM Canopy Walkway is one of the main attractions for visitors at the Forest Research Institute Malaysia (FRIM). Since its opening in 1992, the walkway has recorded visitations from all over the world thus bringing good revenues to FRIM's management. This study was conducted to assess visitors' perception towards the attractiveness of FRIM Canopy Walkway as a nature-based tourism product. Questionnaires were distributed to the visitors within a 4 months period whereby a total of 372 surveys were completed. The conceptual framework was constructed based on the Fishbein's Multi-attribute Model. The results indicated that the model provides beneficial means for the evaluation on multiple attributes as well as measurement on the attractiveness of FRIM canopy tourism product. From this approach, it was revealed that the most attractive factor of FRIM Canopy Walkway is the 'view from the walkway'. FRIM's management, particularly the Ecotourism and Urban Forestry Programme that is responsible in managing the walkway can use the findings to their advantage in deciding on the best marketing strategies and management practices required concerning the sustainability of FRIM Canopy Walkway as a nature-based tourism product.